An apodization method for guided-mode resonance grating with waveguide cavity. (1st August 2022) - Watanabe, Akari; Ozawa, Keisuke; Ueda, Ryohei; Inoue, Junichi; Kintaka, Kenji; Ura, Shogo
Abstract: A cavity-resonator-integrated guided-mode resonance mirror (CRIGM) consisting of a small-aperture grating coupler integrated in a waveguide cavity on a high-reflection substrate reflects an incident free-space wave with reflection-phase variation of 2 π in a resonance condition. CRIGM has been investigated as a key component in surface mount packaging of VCSEL for future optical interconnects but the reflectance of a fabricated CRIGM was not sufficient. Matching of electric field distribution between an incident Gaussian beam and the reflected beam from the CRIGM is discussed for improving the reflectance. A new apodization method of grating-tooth shift is proposed for the field-distribution matching. CRIGMs with the new and a well-known fill-factor apodization methods are characterized by numerical simulation. It is predicted that the previously measured reflectance will be improved by more than 1.2 dB by introducing either of the apodization methods.